Haloed Hallucinations: Vladimir Nabokov’s Bend Sinister and the Cult of St. Antony from Athanasius to Gustave Flaubert - Eklund, Erik (Religion and the arts, 2023)
Among the most popular hagiographies throughout Eastern and Coptic Christianity, Athanasius’ Life of Antony has exercised profound influence upon Western visual and literary art, not least Vladimir Nabokov’s Bend Sinister. Querying the alleged originality of Nabokov’s “symbol of the Divine power,” this article examines Nabokov’s engagement with the Antonian hagiographic tradition—represented by Athanasius’ Life, Hieronymus Bosch’s Triptych of the Temptation of St. Anthony, and Gustave Flaubert’s Le Tentation de saint Antoine—to reveal the religious ground of protagonist Adam Krug’s saint-like identity and the novel’s metaliterary mysticism in the Lord’s figural descent upon an inclined beam of light at the end of Antony’s temptations. Providing a transgressive theological terroir for Nabokov to probe the porous varieties of the real, the Antonian sources of Krug’s “haloed hallucination” invite further reconsideration of Nabokov’s self-styled “indifference” to the Christian imaginary.